A randomised trial of domiciliary, ambulatory oxygen in patients with COPD and dyspnoea but without resting hypoxaemia. Issue 1 (29th September 2010) - Moore, Rosemary P; Berlowitz, David J; Denehy, Linda; Pretto, Jeffrey J; Brazzale, Danny J; Sharpe, Ken; Jackson, Bruce; McDonald, Christine F
Abstract : Background: Patients with chronic obstructive pulmonary disease (COPD) who are not severely hypoxaemic at rest may experience significant breathlessness on exertion, and ambulatory oxygen is often prescribed in this circumstance despite a lack of conclusive evidence for benefit. This study aimed to determine whether such patients benefit from domiciliary ambulatory oxygen and, if so, which factors may be associated with benefit. Methods: This was a 12 week, parallel, double-blinded, randomised, placebo-controlled trial of cylinder air versus cylinder oxygen, provided at 6 l/min intranasally, for use during any activity provoking breathlessness. Patients underwent baseline measurements of arterial blood gases and lung function. Outcome measures assessed dyspnoea, health-related quality of life, mood disturbance, functional status and cylinder utilisation. Data were analysed on an intention-to-treat basis, p≤0.05. Results: 143 subjects (44 female), mean±SD age 71.8±9.8 years, forced expiratory volume in 1 s (FEV1 )1.16±0.51 lites, Pao 2 9.5±1.1 kPa (71.4±8.5 mm Hg) were randomised, including 50 patients with exertional desaturation to ≤88%. No significant differences in any outcome were found between groups receiving air or oxygen. Statistically significant but clinically small improvements in dyspnoea and depression were observed in the whole study group over the 12 weeks of the study. Conclusion: In breathless patients with COPD who do not have severe resting hypoxaemia, domiciliary ambulatory oxygen confers no benefits in terms of dyspnoea, quality of life or function. Exertional desaturation is not predictive of outcome. Intranasal gas (either air or oxygen) may provide a placebo benefit. Clinical trial number: ACTRN12605000457640.